2022
DOI: 10.1007/s12325-022-02369-x
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utility Mapping of Rimegepant for the Preventive Treatment of Migraine: Double-Blind Treatment Phase and Open Label Extension (BHV3000-305)

Abstract: Introduction:The objectives of this study were to (1) report long-term health-related quality of life (HRQoL) outcomes among patients using rimegepant preventatively in BHV3000-305 (NCT03732638) open-label extension (OLE) and (2) map Migraine-Specific Quality of Life questionnaire version 2.1 (MSQv2) to EQ-5D-3L utility values over the double-blind treatment (DBT; 0-12 weeks) and the OLE (13-64 weeks) to assess the influence of treatment on these values. Methods: This was a post hoc analysis using data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As a health state utility mapping of rimegepant for the preventive treatment of migraine, a secondary evaluation of trial BHV3000-305 conducted by Croop et al [14] was designed to analyze the outcomes of long-term health-related quality of life of the rimegepant group with 4-18 MMDs in an open-label extension period and to map MSQv2 to EQ-5D-4 L utility values over the 12-week-long double-blind treatment and open-label extension (13-64 weeks) periods. The results showed that rimegepant was superior to placebo in the double-blind treatment phase, revealed a similar improvement in MSQv2, and mapped health state utility values in both trial arms (originally taking either verum or placebo) over the 52week open-label extension phase, where all patients were on rimegepant 75 mg every other day [59].…”
Section: Rimegepant 2211 Results From Rctsmentioning
confidence: 90%
“…As a health state utility mapping of rimegepant for the preventive treatment of migraine, a secondary evaluation of trial BHV3000-305 conducted by Croop et al [14] was designed to analyze the outcomes of long-term health-related quality of life of the rimegepant group with 4-18 MMDs in an open-label extension period and to map MSQv2 to EQ-5D-4 L utility values over the 12-week-long double-blind treatment and open-label extension (13-64 weeks) periods. The results showed that rimegepant was superior to placebo in the double-blind treatment phase, revealed a similar improvement in MSQv2, and mapped health state utility values in both trial arms (originally taking either verum or placebo) over the 52week open-label extension phase, where all patients were on rimegepant 75 mg every other day [59].…”
Section: Rimegepant 2211 Results From Rctsmentioning
confidence: 90%
“…Our results also showed that using a disease-specific HRQOL questionnaire can sometimes be more sensitive in capturing the health utilities compared with the generally accepted EQ-5D-5L, especially in diseases with a paroxysmal nature such as migraine, where the period of awareness of symptoms can be short. This leads to higher utility values when using the EQ-5D, compared with questionnaires with a longer recall period like the MSQ [ 34 ]. This is likely not specific to our data as it was confirmed by two other studies in EM and CM patients that were conducted in the UK [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the gepants, both atogepant and rimegepant were tested for migraine prevention. 101 102 103 Atogepant seems to be the most promising of this class of drugs, since it bears the best efficacy data 101 104 105 106 107 108 109 and was described as effective also for preventing chronic migraine. 110 Table 4 summarizes the clinical pharmacology of the available gepants.…”
Section: The Antimigraine Drugsmentioning
confidence: 99%